1983
DOI: 10.1111/j.1465-7295.1983.tb00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Performance of U.S. Trunk and Local Servce Airlines in the Era of Deregulation

Abstract: The transition to deregulation of the U.S. air transport industry began in 1976. In this paper we measure total factor productivity growth of the airlines for the first five years of the transition (1976–1980) and compare the performance with that of the preceding years. We find that productivity growth accelerated from 2.8% per year to 5.1% per year. An analysis of covariance model with individual airlines as observations leads to the conclusion that for the trunk airlines nearly all of the acceleration can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 4 publications
(1 reference statement)
0
25
0
1
Order By: Relevance
“…Estudos seminais da área encontram-se em Caves et al (1983), que compararam o desempenho da produtividade de 11 companhias aéreas com base nas taxas de crescimento. Oum et al (2005) verificaram o desempenho de 10 companhias aéreas americanas, a partir de uma análise comparativa dos anos de 1990 a 2000, recorte temporal justificado pelos acontecimentos econômicos mundiais vivenciados pelo país no período.…”
Section: Medidas De Desempenho Como Resultado Da Eficiência Operacionalunclassified
“…Estudos seminais da área encontram-se em Caves et al (1983), que compararam o desempenho da produtividade de 11 companhias aéreas com base nas taxas de crescimento. Oum et al (2005) verificaram o desempenho de 10 companhias aéreas americanas, a partir de uma análise comparativa dos anos de 1990 a 2000, recorte temporal justificado pelos acontecimentos econômicos mundiais vivenciados pelo país no período.…”
Section: Medidas De Desempenho Como Resultado Da Eficiência Operacionalunclassified
“…Most of the empirical research has concerned the United States, at first inspiring the 1978 domestic airline reforms and later looking at the economic implications of liberalisation and enhanced competition (Caves et al, 1983;Bailey et al, 1985;Liu and Lynk, 1999). 1 US research also demonstrated that certain feared outcomes of liberalisation -such as declines in safety levels, or deprivation of small communities of air service -did not materialise.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of anticipated relationships and expected signs, studies by Caves et al (1983) and others have shown evidence of a positive correlation between average load factors and financial performance while Oum and Yu's work (1999) suggests that average load factor is a reflection of an airline's choice of aircraft and flight frequencies. Fethi et al (2002) find that an increase in the international focus of an airline leads to spatial disparities in its financial environment.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 94%